Digitalisasi Profil Desa Turus - Sri Hilmi Pujihartati; Hasna Amila Mahmudah; Gigih Pratiwi; Hersa Ameilia Ridhani; Ihza Aulia Alfarisi; Immanuel Jeremia Sarjono; Irfan Ferli Angga; Isnan Nur Safitri; Zunus Auri; Fullaikhah Anjani; Ersya Nissa Ardalia (Jurnal Pengabdian Pada Masyarakat, 2022)
DIGITALISATION OF TURUS VILLAGE’S. Turus Village is one of the villages located in Polanharjo District, Klaten Regency, Central Java Province. Turus Village has various kinds of potential in the form of extensive rice fields, various food processing MSME products, service businesses and culture. However, the potential of the village of Turus has not been exposed to the wider community. There is no media that can broadcast the potential of Turus Village. In a community service program entitled Thematic Community Service Program to Build Villages at Sebelas Maret University, we took the initiative to help the Turus village government in managing the digitization of village profiles and their potential. This program includes making village websites, making village profile videos and digitizing village archives. The purpose of this program is to provide media information to Turus Village so that it can be better known by the wider community, existing potentials can be known to the general public and it is possible that in the future it will be able to bring in investors to manage Turus Village potentials. which can encourage the Turus Village economy to be more advanced